(E)-Vinylphosphonates: nuclease-stable phosphate mimics for effective single-stranded RNA gene silencing - Al-Kadhimi, Mustafa M. (2020)
The therapeutic efficacy of double-stranded short interfering RNAs (ds-siRNAs) is limited by the formation of the lipid complex to deliver them to cells. Whereas if effective single-stranded siRNAs (ss-siRNAs) could be developed, they would offer an easier way of delivery and they can be produced at half price. Chemical modifications to ss-siRNAs are required to improve gene-silencing efficacy in vivo and to enhance their nuclease stability. This study describes a synthetic route that can access all the possible combinations of the modified (E)-vinylphosphonate ((E)-VP) linked-dinucleotides. Additionally, it demonstrates a method to synthesise a ss-siRNA contain a single 5′-terminus (E)-vinyphosphonate (5′-(E)-VP) using the standard phosphoramidite method that does not require additional deprotection steps. The study shows that the vinylphosphonate is well tolerated in the 5′-terminus between nucleotide 1 and nucleotide 2 of the ss-siRNA, and that shown efficient in vitro and in vivo knockdown of luciferase in MDA-MB fluc cells in comparison to a negative control.